Case Report: A renal wasting disease caused by a pure deletion of nephrocystin-1 - Dong, Ting; Luo, Jiajia; Sun, Tianhong; Wu, Huimin; Zhao, Qing; Ma, Lina; Yang, Jing (Frontiers in Pediatrics, 2025)
Nephronophthisis is an autosomal recessive disorder associated with the tubular interstitium of the kidney, and can lead to renal failure in children and adolescents. Mutations in the gene encoding nephrocystin-1, NPHP1, are frequently associated with the disease. Here, we describe the case of a child who presented to the clinic with febrile convulsions and who was ultimately diagnosed with nephronophthisis caused by a homozygous deletion of the NPHP1 gene. Alerting pediatricians to the recognition of atypical renal wasting disease and reclarifying the diagnostic value of genetic diagnosis for this disease.